2014
DOI: 10.1128/genomea.00713-14
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Pseudomonas mandelii PD30

Abstract: The genome sequence of Pseudomonas mandelii PD30 is reported in this announcement. The genes for the reduction of nitrate to dinitrogen were identified in the genome assembly and subsequently used in gene expression research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Figure 3 shows the ANIb values of all the 24 pseudomonads used in this study, which were in good agreement with those of ANIm ( Figure S8 ). The highest ANIb values for TNT3 and TNT19 were observed when these isolates were compared to P. mandelii PD30 (denitrifying bacterium) [ 71 ] and P. frederiksbergensis AS1 (aromatic degrader) [ 72 ], respectively, both reaching near 86% identity (clearly below the 95% threshold). Regarding TNT11, the highest ANIb value was observed when it was compared to P. veronii 1YdBTEX2 (aromatics degrader) [ 68 ], reaching nearly 94% identity (very close to the 95% threshold).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows the ANIb values of all the 24 pseudomonads used in this study, which were in good agreement with those of ANIm ( Figure S8 ). The highest ANIb values for TNT3 and TNT19 were observed when these isolates were compared to P. mandelii PD30 (denitrifying bacterium) [ 71 ] and P. frederiksbergensis AS1 (aromatic degrader) [ 72 ], respectively, both reaching near 86% identity (clearly below the 95% threshold). Regarding TNT11, the highest ANIb value was observed when it was compared to P. veronii 1YdBTEX2 (aromatics degrader) [ 68 ], reaching nearly 94% identity (very close to the 95% threshold).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, species isolated from Juan Carlos I Station were related to P. mandelii. P. mandelii is a psychrotolerant bacterium characterized by it s met ab o lic versatility, plasticity, and biotechnological potential [33]. This bacterium was first isolated from mineral water in France [34] and it was also identified in mineral water samples from South Korea, and soil samples from China, United States, and Canada [33].…”
Section: B Isolation Of Bacteria Producing Cold-active Enzymesmentioning
confidence: 99%
“…P. mandelii is a psychrotolerant bacterium characterized by it s met ab o lic versatility, plasticity, and biotechnological potential [33]. This bacterium was first isolated from mineral water in France [34] and it was also identified in mineral water samples from South Korea, and soil samples from China, United States, and Canada [33]. Previous studies have reported the isolation of P. mandelii from Antarctic soils in King George Island [22] and Deception Island [20].…”
Section: B Isolation Of Bacteria Producing Cold-active Enzymesmentioning
confidence: 99%
“…Discussion. For the first time P. mandelii was isolated from mineral waters in France [23] and Korea [24], soils in China [25], river sediments from the Aldan River in the Central Yakutia region of Siberia [26], and in potato crop waters in New Brunswick, Canada [27].…”
Section: F I G 3 Pyrogenic Activity Of Lps Preparations Of P Mandelii U1 After Administrationmentioning
confidence: 99%